Kolaborasi Camat, Koramil, dan Polsek untuk Meningkatkan Keamanan dan Ketertiban di Kecamatan Amanatun Utara - Julianto Linome; Umbu T.W Pariangu; Belandia L. Long; Rouwland A. Benyamin (Atmosfer: Jurnal Pendidikan, Bahasa, Sastra, Seni, Budaya, dan Sosial Humaniora, 2026)
This study examines the collaboration among the Subdistrict Head (Camat), the Indonesian National Armed Forces (Koramil), and the Indonesian National Police (Polsek) in maintaining public security and public order in Amanatun Utara Subdistrict, South Central Timor Regency. The research was motivated by the increasing complexity of public security issues that require Collaborative governance among government institutions and security agencies. A qualitative descriptive approach was employed, with data collected through in-depth interviews, observation, and document analysis involving key stakeholders from the subdistrict government, military, police, village governments, traditional leaders, and community representatives. Data were analyzed using the interactive model of Miles, Huberman, and Saldaña, while the analytical framework was based on the Collaborative governance model proposed by Ansell and Gash. The findings reveal that collaboration has generally functioned effectively through adaptive communication, shared commitment, and clear institutional responsibilities. The presence of Babinsa and Bhabinkamtibmas, mutual trust among institutions, and supportive legal frameworks constitute the main enabling factors. However, collaboration remains constrained by limited human resources, insufficient operational funding, inadequate infrastructure, weak community-based security systems, and the absence of an integrated early warning mechanism. Strengthening institutional coordination, expanding community participation, and improving resource support are therefore essential to enhance sustainable Collaborative governance in maintaining public security.